Informed Decision Making for Anticoagulation Therapy for Atrial Fibrillation. (February 2023) - Martinez, Kathryn A.; Linfield, Debra T.; Shaker, Victoria; Rothberg, Michael B.
Background: Patients with atrial fibrillation (AF) must decide between warfarin and direct oral anticoagulants (DOACs), a decision involving important tradeoffs. Our objective was to understand whether physicians engage patients in informed decision making for anticoagulants. Design: We performed an analysis of recorded conversations between physicians and anticoagulation-naïve patients in the Verilogue Point-of-Practice database. We assessed the presence of 7 elements of informed decision making, as well as a discussion of financial costs. Results: Of 37 encounters with 21 physicians, 92% resulted in a DOAC prescription and 8% resulted in a warfarin prescription. Seventy percent met criteria for discussion of pros and cons, 70% for discussion of the alternatives, 43% presented the decision, 30% included an assessment of patient understanding, 22% included an explanation of the patient's role in decision making, 22% included an assessment of patient preferences, and 19% included a discussion of uncertainty. Two encounters (5%) included all 7 elements and 9 (24%) included none. Physicians discussed treatment costs with patients in 43% of encounters. Limitations: We assessed informed decision making in a single encounter. Physicians and patients may have had other discussions that were not captured in our data. Conclusions: Physicians often presented the alternatives but did not generally engage patients in informed decision making. The high rate of DOAC prescriptions is likely the result of physician preferences, as patient preferences were rarely assessed. Implications: Strategies to support physicians in engaging patients in informed decision making for anticoagulation are needed. Highlights: While physicians discussed the alternatives and presented pros and cons with patients, they rarely assessed patient preferences, explained the patient's role in decision making, or addressed uncertainty. The cost of treatment with DOACs versus warfarin was discussed by physicians in less than half of encounters, limiting patients' ability to make informed decisions for anticoagulation. Only 2 encounters (5%) fulfilled all 7 elements of informed decision making.